PENGARUH KUALITAS LAYANAN, HARGA, DAN KEMUDAHAN TERHADAP KEPUASAN PELANGGAN TRI DI SURABAYA - IQBAL TAWAKAL, DENI (Jurnal Ilmu Manajemen (JIM), 2016)
This study aims to analyze and discuss the influence of service quality, price, and ease of use on customer satisfaction of Tri . This type of research is quantitative. Samples taken as many as 210 respondents. Measuring tool used was a questionnaire. Analysis of data by multiple linear regression model were analyzed using SPSS 20 software. The results showed that the influence on the quality of service satisfaction, the price effect on satisfaction, ease of use on the satisfaction of 22.1%. Keywords: Service Quality, Price, Ease Of Use, Customer Satisfaction